2015
DOI: 10.1097/iae.0000000000000582
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Choroidal Thickness and Body Mass Index

Abstract: We have demonstrated that BMI may have an influence on the CT of healthy persons. Individuals in both Group 3 and Group 4 have thinner choroids than the individuals in both Group 1 and Group 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 29 publications
3
50
1
Order By: Relevance
“…Ikuno et al 31 showed that aging is a factor associated with changes in choroidal thickness; older patients are reported to have thinner choroids. Yilmaz et al 32 have demonstrated that the body mass index may have an influence on the choroidal thickness of healthy persons: individuals with high body mass index have thinner choroids than individuals with low body mass index. Tan et al 33 reported a significant diurnal variation in choroidal thickness, and Usui et al 34 reported that there was a correlation between diurnal systolic BP fluctuation and choroidal thickness fluctuation.…”
Section: Discussionmentioning
confidence: 99%
“…Ikuno et al 31 showed that aging is a factor associated with changes in choroidal thickness; older patients are reported to have thinner choroids. Yilmaz et al 32 have demonstrated that the body mass index may have an influence on the choroidal thickness of healthy persons: individuals with high body mass index have thinner choroids than individuals with low body mass index. Tan et al 33 reported a significant diurnal variation in choroidal thickness, and Usui et al 34 reported that there was a correlation between diurnal systolic BP fluctuation and choroidal thickness fluctuation.…”
Section: Discussionmentioning
confidence: 99%
“…However, CT may be influenced by a broad spectrum of factors such as age,12 25–27 axial length,4 12 26 27 systemic blood pressure,28 ocular perfusion pressure,29 diurnal fluctuations,30 31 smoking,32 anterior chamber depth,12 lens thickness,12 corneal curvature,12 obstructive sleep apnoea syndrome,33 body mass index,34 use of phosphodiesterase inhibitors35 and others.…”
Section: Discussionmentioning
confidence: 99%
“…Our study of a healthy north Indian population showed a mean subfoveal choroidal thickness of 325.18 ± 47.087 µm with a mean age of 33.60 years, which was more than a Korean population [21](307.3±95.2 µm) with a mean age of 40.18 years, an adult Spanish population [22] (305.6±102.6 µm) with a mean age of 53 years and a Chinese population [23] (261.9±88.4 µm) with a mean age of 49.73 years and lesser than a Japanese population [24] (354± 111 µm) with a mean age of 39.4 ±16.0, a mixed ethnic population of UK [25] (332 ± 90µm) with a mean age of 24.46 ± 1.12 and a Turkish population [26] in which the mean subfoveal CT was 348 ± 68 µm. The differences in mean subfoveal choroidal thickness may result from differences in the mean age of each study.…”
Section: Discussionmentioning
confidence: 99%